Study of the Implementation of Health Management for Pig Breeding in CV Roku, Manggarai, East Nusa Tenggara - Rinca, Korbinianus Feribertus; Gultom, Roselin; Luju, Maria Tarsisia; Febrizki Bollyn, Yohana Maria; Achmadi, Puspita Cahya; Utama, Wigbertus Gaut (Jurnal Ilmu Ternak Universitas Padjadjaran, 2024)
The application of health management is a determining factor for the success of a pig farm business. This research was conducted to find out the implementation of pig health management in CV. Roku, Manggarai, East Nusa Tenggara. The data used in this research was secondary data. The secondary data was reconfirmed to the owner using the direct interview method using questionnaires. Secondary data that has been confirmed using the interview method, was then analyzed descriptively. The practice of health management studied was the application of medication, biosecurity, and vaccination to gilts, sows, and piglets. The results of the study showed that the treatment of gilts reared on the farm was in the form of giving antibiotics, vitamins, and anthelmintics; medical measures performed on sows after giving birth in the form of giving antibiotics, vitamins, and anti-inflammatories while medical measures for sows after weaning are in the form of vitamins and antibiotics; as well as medical measures for piglets reared in the farm in the form of iron (Fe), vitamins, and antibiotics. The results of this study could be concluded that CV. Roku has not properly implemented pig health management, as evidenced by CV. Roku only applies medication but didn't apply biosecurity and vaccination at all to gilts, sows, and piglets in health management.